(untitled) (Bangladesh Critical Care Journal, 2019)
Background : This study is a sub analysis of data submitted on behalf of Bangladesh to an international study (2013-2014) involving Asian ICUs and merits comparison with prior study done in Bangladesh in 2007 which had similar objective. Objective : To assess structure, organization and delivery of ICU care in ICUs of Bangladesh with attention to hospital organizational characteristics, ICU organizational characteristics, staffing etc. Method : Prospective cohort study involving ICUs of 51 hospitals of Bangladesh done in 2013-2014. The hospitals in our study were divided into three groups : clinics/hospitals less than 50 beds (n =18), clinics/hospitals more than 50 beds(n=24) and Govt. hospitals/academic hospitals/ medical colleges hospitals (n=9). Results : Most respondent hospitals were from Dhaka (77.4%). Only 17.6% hospitals were university affiliated. The average number of hospital beds were 225. The average number of ICU beds were 14. 19.6 % hospitals had infection control committees. Basic life support training was required for doctors and nurses in 31.4 % and 27.5 % hospitals respectively. Small clinics/ hospitals (less than 50 bed capacity [n=18]) had significantly less government funding (p < 0.0001), were less attached to university hospital (p < 0.0001), had fewer referral centers (p < 0.001), had less total hospital beds (p < 0.004) and were less in case of ICU beds : hospital beds percentage (p < 0.003). 28 ICUs had no single room. Govt. hospitals/academic hospitals/Medical colleges had relatively more ICU beds .(12.33% - p < 0.004). 60.8% ICUs were operated as open units. Open units were more likely present in hospitals/clinics more than 50 beds. Multivariable analysis showed that the presence of 1:1 nursing staff was much lower in private hospitals. Funding sources and types of hospitals were independently associated with lower percentage of ICU beds (p < 0.002) and (p < 0.0001) respectfully. University affiliations was more likely associated with closed ICU (p < 0.002). Presence of MD CCM qualified intensivists are more in government funded hospitals (p < 0.003) than those of private hospitals Conclusions : Our study demonstrates considerable variation in the organization and staffing among Bangladeshi ICUs. Compared to 2007 study it shows increased trend in number of closed units( 39% vs 15%) and percentage of ICU beds relative to number of hospital beds (6.5% vs 4.8%) . Bangladesh Crit Care J March 2019; 7(1): 3-11